Enhanced control of complex production structures by tight coupling of the digital and the physical worlds - Kádár, B.; Lengyel, A.; Monostori, L.; Suginishi, Y.; Pfeiffer, A.; Nonaka, Y. (CIRP annals, 2010)
Unexpected disturbances and local decisions almost always deteriorate the execution of manufacturing plans. Digital enterprise technologies are hard to use, due to the complexity of production and the frequently changing circumstances. One of the main goals of the research described in the paper is the automatic model building of the discrete-event simulation system, based on intelligent analysis of the huge amount of information incorporated in the production database. The developed solution supports shop-floor dispatching and shop-floor managers in making control decisions.